Reference equations of oxygen uptake for the step test in the obese population - Fagundes,C.F. (2022)
The aim of this study was to establish reference equations for the six-minute step test (6MST) based on demographic, anthropometric, body composition, and performance variables able to predict oxygen uptake (V̇O2) in obese individuals. Seventy-three obese adults (42±14 years old, body mass index >30 kg/m2) from both sexes were included. They underwent anamnesis, body composition evaluation, and the 6MST with expired gases registered simultaneously. Three equations were developed for the obese population (n=73; 59% female). The first equation was composed of the up-and-down step cycles (UDS), sex, and age as predictors; the second equation was composed of the UDS, age, and lean mass (LM). Both equations collectively explained 68.1% of the V̇O2 variance in the 6MST, while the third equation, composed of the UDS, age, and body mass, accounted for 67.7% of the V̇O2 variance. UDS, sex, age, LM, and body mass were important V̇O2 predictors of 6MST in these obese individuals. This study contributes to the dissemination of a simple, inexpensive, and fast evaluation method that can provide important indicators of cardiorespiratory fitness and guide strategies for rehabilitation.